Climate Change Risk and Green Low-Carbon Development in Agriculture: Evidence from China on the Regulatory Role of Agricultural Insurance and Spatial Spillover Effects - ZHAOYANG LU (21957038) (2025)
This study uses panel data from 31 provinces in China for the period 2003–2023. The specific data sources and processing methods are as follows: Climate Risk Data The climate risk index is calculated using the dataset provided by NOAA (NOAA Dataset). Other Variables Data Other variable data are sourced from the China Population and Employment Statistical Yearbook, the China Insurance Statistical Yearbook, and other relevant statistical yearbooks. Missing data were filled using linear interpolation.